Phase difference film, polarizing plate, and display device

CN122962707APending Publication Date: 2026-10-23FUJIFILM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610469428.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-03-04
Filing Date
2026-04-10
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

本发明人将专利文献1中所记载的起偏器应用于上述用途的结果,发现了无法获得所期望的效果

Benefits of technology

[0008]根据本发明,能够提供一种相位差膜,其能够通过将偏振片与起偏器组合来形成,该偏振片在作为显示装置的防反射膜应用时,能够降低反射率且能够抑制黑色显示时的色调不均匀。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

The present application provides a phase difference film, a polarizing plate, and a display device, which can be formed by combining a polarizing plate with a polarizer, and which, when applied as an antireflection film of a display device, can reduce reflectance and can suppress color unevenness during black display. A phase difference film is a phase difference film formed using a composition containing a compound represented by formula (I), wherein the in-plane retardation at a wavelength of 550 nm is 100 to 180 nm, the in-plane retardation Re(450) at a wavelength of 450 nm and the in-plane retardation Re(550) at a wavelength of 550 nm satisfy the relationship of formula (X), and the birefringence Δn of the phase difference film at a wavelength of 550 nm is 0.040 to 0.070. Formula (X) Re(450) / Re(550) ≤ 1.00 Formula (I) R 1 - (A 1 - L 1 ) m1 - G - (L 2 - A 2 ) m2 - R 2 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a phase difference film, a polarizer, and a display device. Background Technology

[0002] Phase retardation films formed using liquid crystal compounds are suitable for various applications. For example, it is known to combine phase films with polarizers to use them as polarizers. For example, Patent Document 1 discloses a polarizer comprising a phase retardation layer formed using a specified liquid crystal compound.

[0003] Patent Document 1: Japanese Patent No. 7205981

[0004] One application of polarizers is as an anti-reflective film for display devices. In the above applications, when a polarizer is used as an anti-reflective film for a display device, it is desirable to have low reflectivity and to suppress color unevenness when the display device displays black. When the inventors applied the polarizer described in Patent Document 1 to the above-mentioned applications, they found that the desired effect could not be obtained. Summary of the Invention

[0005] The objective of this invention is to provide a phase difference film that can be formed by combining a polarizer with a polarizer. When used as an anti-reflective film for a display device, the polarizer can reduce reflectivity and suppress uneven color tone when displaying black. Furthermore, the present invention also aims to provide a polarizer and a display device.

[0006] In order to solve the above-mentioned problems, the inventors conducted in-depth research and completed the present invention with the following structure.

[0007] (1) A phase retardation film, which is a phase retardation film formed using a composition comprising a compound represented by formula (I) as described below, wherein, The in-plane retardation at a wavelength of 550 nm is 100–180 nm. The in-plane delay Re(450) at a wavelength of 450 nm and the in-plane delay Re(550) at a wavelength of 550 nm satisfy the relationship of equation (X) described later. The birefringence Δn of the phase retardation film at a wavelength of 550 nm is 0.040–0.070. (2) The phase difference film according to (1), wherein the composition further contains a compound with positive wavelength dispersive properties. (3) According to the phase difference film described in (2), wherein the birefringence Δn of the positive wavelength dispersive compound at a wavelength of 550 nm is 0.050 to 0.100. (4) The phase difference film according to any one of (1) to (3), wherein the composition contains two or more compounds represented by formula (I). (5) The phase difference film according to any one of (1) to (4), wherein the composition further comprises a multifunctional monomer. (6) The phase difference film according to any one of (1) to (5), wherein the composition further comprises a polyfunctional thiol compound. (7) The phase difference film according to any one of (1) to (6), wherein the content of the compound represented by formula (I) is less than 85% by mass relative to the total solid content in the composition. (8) The phase difference film according to any one of (1) to (7), wherein the composition further comprises an oxime initiator. (9) The phase difference film according to any one of (1) to (8), wherein the composition further comprises a leveling agent. The leveling agent content is 0.01 to 0.1% of the total mass of the liquid crystal compound in the composition. (10) The phase difference film according to any one of (1) to (9), wherein the residual rate of polymeric groups is less than 30%. (11) A polarizer comprising a phase difference film and a polarizer as described in any one of (1) to (10). (12) The polarizer according to (11) further comprises a positive C plate. (13) The polarizer according to (11) or (12) further comprises an alignment film disposed adjacent to the phase difference film. (14) A display device comprising any one of (11) to (13) a polarizer. Invention Effects

[0008] According to the present invention, a phase difference film can be provided, which can be formed by combining a polarizer with a polarizer. When the polarizer is used as an anti-reflective film for a display device, it can reduce reflectivity and suppress color unevenness when displaying black. The present invention can also provide a polarizer and a display device. Detailed Implementation

[0009] The present invention will now be described in detail. The following description of the constituent elements is sometimes based on representative embodiments and specific examples, but the present invention is not limited to such embodiments. In addition, in this specification, the numerical range indicated by “~” refers to the range included by taking the values ​​recorded before and after “~” as the lower limit and upper limit values.

[0010] In this specification, "absorption axis" refers to the polarization direction in which the in-plane absorbance is greatest when incident on linearly polarized light. Furthermore, "in-plane slow axis" refers to the direction in which the in-plane refractive index is greatest.

[0011] The in-plane delay Re(λ) at wavelength λ was determined using an AxoScan OPMF-1 (manufactured by Opto Science, Inc.). Unless otherwise specified, wavelength λ is 550 nm. Rth(λ), the retardation value in the thickness direction, is calculated using AxoScan OPMF-1, specifically by inputting the average refractive index ((nx+ny+nz) / 3) and the film thickness (d). Rth(λ)=((nx+ny) / 2-nz)×d. The birefringence Δn at a wavelength of 550 nm is calculated using the following formula. Additionally, d represents the thickness (nm) of the retardation film. Furthermore, the birefringence Δn described above is the value at a temperature of 25°C. Birefringence Δn = Re (550) / d

[0012] Furthermore, in this specification, the refractive indices nx, ny, and nz are measured using an Abbe refractometer (NAR-4T, manufactured by ATAGO CO.,LTD.) and a sodium lamp (λ=589nm) as the light source. Additionally, when measuring wavelength dependence, measurements can be performed using a multi-wavelength Abbe refractometer DR-M2 (manufactured by ATAGO CO.,LTD.) in combination with an interference filter. Furthermore, values ​​from the polymer handbook (JOHN WILEY & SONS, INC) and various optical film product catalogs can be used. The following are examples of the average refractive index values ​​for major optical films: cellulose acylate (1.48), cyclic olefin polymer (1.52), polycarbonate (1.59), polymethyl methacrylate (1.49), and polystyrene (1.59).

[0013] In this specification, the A-board and C-board are defined as follows. There are two types of A-plates: positive A-plates and negative A-plates. When the refractive index along the slow axis (where the in-plane refractive index is at its maximum) is set as nx, the refractive index along the direction orthogonal to the slow axis is set as ny, and the refractive index along the thickness direction is set as nz, the positive A-plate satisfies equation (A1), while the negative A-plate satisfies equation (A2). Furthermore, the Rth of the positive A-plate exhibits a positive value, while the Rth of the negative A-plate exhibits a negative value. Equation (A1) nx>ny≈nz Equation (A2) ny<nx≈nz Furthermore, the aforementioned “≈” not only includes cases where the two are completely identical, but also cases where they are substantially identical. “Substantially identical” includes, for example, cases where (ny-nz)×d (where d is the film thickness) is -10 to 10 nm, preferably -5 to 5 nm, and cases where (nx-nz)×d is -10 to 10 nm, preferably -5 to 5 nm, and cases where (nx-nz)×d is -10 to 10 nm, preferably -5 to 5 nm, and cases where nx≈nz. There are two types of C-plates: positive C-plates and negative C-plates. Positive C-plates satisfy the relationship in equation (C1), while negative C-plates satisfy the relationship in equation (C2). Furthermore, a positive C-plate indicates that Rth has a negative value, and a negative C-plate indicates that Rth has a positive value. Equation (C1) nz>nx≈ny Equation (C2) nz<nx≈ny Furthermore, the aforementioned “≈” includes not only cases where the two are exactly the same, but also cases where they are substantially the same. “Substantially the same” means, for example, that even when (nx-ny)×d (where d is the film thickness) is 0 to 10 nm, and preferably 0 to 5 nm, it is included in “nx≈ny”.

[0014] In this specification, solid components in a composition refer to components other than solvents. Furthermore, even if the composition is in liquid form, it is still considered a solid component.

[0015] As a characteristic feature of the phase retardation film of the present invention, it can be cited that the in-plane retardation is within a specified range, it exhibits inverse wavelength dispersion, and the birefringence Δn at a wavelength of 550 nm is within a specified range. First, when the phase retardation film of the present invention is combined with a polarizer to form a polarizer and the polarizer is used as an anti-reflective film for a display device, the polarizer is arranged on the display device in such a way that the phase retardation film in the polarizer is on the display device side. In this structure, when the in-plane retardation of the retardation film is within a specified range, reflectivity can be reduced. Furthermore, when the retardation film satisfies the relationship expressed by equation (X) described later, the retardation film exhibits inverse wavelength dispersion, which can further reduce reflectivity. Furthermore, the inventors discovered that in the above-described method, the unevenness in tone when displaying black is related to wind spots and streaks. To suppress these problems, the birefringence Δn is adjusted to a specified range. More specifically, if the birefringence Δn is too small, the thickness of the retardation film needs to be increased to achieve the specified in-plane delay displayed by the retardation film. In this case, the coating amount is increased to increase the film thickness, and the drying time is also prolonged. As a result, the coating film during drying is easily affected by the surrounding wind, leading to uneven film thickness. Consequently, wind spots, which correspond to uneven film thickness in the retardation film, are generated. These wind spots cause uneven tone when displaying black. Therefore, in this invention, the birefringence Δn of the retardation film is set to 0.040 or higher to suppress the generation of wind spots and reduce uneven tone. Furthermore, when the birefringence Δn of the liquid crystal compound, such as the compound represented by formula (I), used in the formation of the retardation film is large, the birefringence Δn of the retardation film also increases. On the other hand, when the birefringence Δn of the retardation film is too large, the liquid crystal compound itself tends to crystallize due to its structural characteristics. In particular, in order to make the retardation film display a specified in-plane delay, the coating amount of the composition used in the formation of the retardation film is also reduced, thus making crystallization easier. As a result, stripe-like inhomogeneities originating from the crystallization of the liquid crystal compound are generated. Therefore, in this invention, by setting the birefringence Δn of the retardation film to 0.070 or less, stripe-like inhomogeneities are suppressed and color tone inhomogeneities are reduced.

[0016] The phase retardation film of the present invention (hereinafter also simply referred to as "this phase retardation film") is a phase retardation film formed using a composition (hereinafter also simply referred to as "this composition") comprising a compound represented by formula (I) as described later. Furthermore, the in-plane retardation of this phase retardation film at a wavelength of 550 nm is 100–180 nm. Furthermore, the in-plane delay Re(450) of this phase retardation film at a wavelength of 450 nm and the in-plane delay Re(550) of this phase retardation film at a wavelength of 550 nm satisfy the relationship of equation (X) described later. Furthermore, the birefringence Δn of this phase retardation film at a wavelength of 550 nm is 0.040–0.070. The characteristics of this phase retardation film will be described in detail below.

[0017] <Characteristics of this phase retardation film> The in-plane retardation of this retardation film at a wavelength of 550 nm is 100–180 nm. From the viewpoint that the reflectivity can be further reduced when this retardation film is combined with a polarizer to form a polarizer and this polarizer is used as an anti-reflective film for a display device (hereinafter also simply referred to as "the viewpoint of being able to further reduce reflectivity"), 110–165 nm is preferred, and 130–150 nm is more preferred.

[0018] The in-plane retardation Re(450) of this retardation film at a wavelength of 450 nm and the in-plane retardation Re(550) of this retardation film at a wavelength of 550 nm satisfy the relationship of Equation (X). That is, the ratio of the in-plane retardation Re(450) of this retardation film at a wavelength of 450 nm to the in-plane retardation Re(550) of this retardation film at a wavelength of 550 nm is 1.00 or less. Equation (X) represents the characteristic of so-called inverse wavelength dispersion. That is, the retardation film that satisfies the relationship of Equation (X) exhibits inverse wavelength dispersion. Formula (X) Re(450) / Re(550)≤1.00 From the perspective of further reducing reflectivity, this phase difference film preferably satisfies the relationship of equation (X1), and more preferably satisfies the relationship of equation (X2). Equation (X1) Re(450) / Re(550)≤0.93 Formula (X2) Re(450) / Re(550)≤0.87 Furthermore, there is no particular limitation on the lower limit of the ratio of the in-plane delay Re(450) of the phase retardation film at a wavelength of 450 nm to the in-plane delay Re(550) of the phase retardation film at a wavelength of 550 nm. Preferably, the phase retardation film satisfies the relationship of Equation (Y), and more preferably, it satisfies the relationship of Equation (Y1). Formula (Y) Re(450) / Re(550)≥0.70 Equation (Y1) Re(450) / Re(550)≥0.80

[0019] The birefringence Δn of this phase retardation film is 0.040–0.070 at a wavelength of 550 nm. The birefringence Δn is the so-called refractive index anisotropy. From the viewpoint that combining this phase difference film with a polarizer to form a polarizer and using this polarizer as an anti-reflective film for a display device can further reduce tonal unevenness when displaying black (hereinafter, also simply referred to as "the viewpoint that can further suppress tonal unevenness"), a value of 0.050 to 0.058 is preferred. Furthermore, as will be explained in detail later, there are no particular limitations on the method for adjusting the birefringence Δn of this phase retardation film at a wavelength of 550 nm. Methods for adjusting the type and content of the compound represented by formula (I) and other components (e.g., positive wavelength dispersive compounds, multifunctional monomers, and multifunctional thiols, described later) can be cited. In addition to the materials used, the birefringence Δn of this phase retardation film can also be adjusted based on the reactivity of the polymerizable groups contained in the composition. Regarding liquid crystal compounds such as those represented by formula (I), the lower the reactivity of the polymerizable groups, the higher the birefringence Δn of the obtained phase retardation film tends to be. In other words, the higher the residual rate of polymerizable groups in the phase retardation film, the higher the birefringence Δn of the obtained phase retardation film tends to be. Therefore, the birefringence Δn of this phase retardation film can also be adjusted by adjusting the type of polymerization initiator used and the curing conditions.

[0020] The phase retardation film is preferably a film formed by curing the present composition, and more preferably a film formed by orienting and fixing the liquid crystal compound in a coating film formed by coating the present composition. That is, the phase retardation film is preferably a film in which the liquid crystal compound is fixed in a predetermined orientation state. Furthermore, once it becomes a film, there is no need to display liquid crystal properties. As an example of the aforementioned fixing method, a method for orienting and curing a liquid crystal compound having polymerizable groups can be cited. There are no particular restrictions on the orientation state of the fixed liquid crystal compound in this phase difference film, but uniform orientation is preferred. The phase difference film is preferably plate A, and more preferably positive plate A.

[0021] In this phase difference film, the residual rate of polymeric groups is preferably less than 30%. The residual rate of the polymeric groups mentioned above represents the proportion of polymeric groups contained in this composition that remain in the phase difference film. That is, it is the proportion (%) calculated by the following formula. Residual rate of polymeric groups = (Amount of polymeric groups in the phase retardation film / Amount of polymeric groups in the composition) × 100 The lower the residual rate value, the more the polymeric groups are consumed when using this composition to form a phase difference film. The residual rate of the aforementioned polymerizable groups can be calculated, for example, by infrared spectroscopy. For instance, if the polymerizable group is acryloyl or methacryloyl, and infrared spectroscopy is applied to the coating film formed using the composition before polymerization, the residual rate at 1408 cm⁻¹ will be [data missing]. -1Absorption peaks originating from C=C groups were identified nearby. Similarly, infrared spectroscopy was used on the phase retardation film to confirm the presence or absence of these absorption peaks. The residual rate of polymeric groups can be calculated based on the ratio of the area of ​​the absorption peak of the coating film to the area of ​​the absorption peak of the phase retardation film. Furthermore, when performing the above calculations, peaks whose size did not change during the formation of the phase retardation film can be used as a reference, if necessary. Furthermore, when calculating the residual rate of polymeric groups using infrared spectroscopy on the above-mentioned coating and phase retardation film, the residual rate is calculated on one main surface of the phase retardation layer corresponding to main surface A of the coating and the two main surfaces of the phase retardation film obtained after coating curing, and the residual rate is calculated on the other main surface B of the coating and the other main surface of the phase retardation layer corresponding to main surface B of the phase retardation film obtained after coating curing. The value obtained by averaging the two calculated residual rates is taken as the residual rate of polymeric groups of the present invention.

[0022] The thickness of this phase retardation film is not particularly limited, but from the viewpoint of thinning, it is preferably 10 μm or less, and more preferably 0.1 to 5.0 μm. Furthermore, the thickness of this retardation film refers to its average thickness. This average thickness is obtained by measuring the thickness of any five or more points on the retardation film and then taking their arithmetic average. The thickness measurement can be performed, for example, using a reflective beam-splitting thickness gauge FE3000.

[0023] <This composition> This phase retardation film is formed using this composition. The components contained in this composition are described in detail below.

[0024] (Compounds represented by formula (I)) This composition contains a compound represented by formula (I). Formula (I) R 1 -(A 1 -L 1 ) m1 -G-(L 2 -A 2 ) m2 -R 2 The following is a detailed description of each group.

[0025] In the formula, R 1 and R 2 Each of the following groups independently represents a straight-chain or branched alkyl group having 1 to 12 carbon atoms, wherein one -CH2- or two or more non-adjacent -CH2- groups may be independently replaced by -O-, -COO-, -OCO- or -O-CO-O-, or by a group represented by formula (II). Among them, R1 and R 2 At least one of them represents a group represented by formula (II). Among them, R is preferred. 1 and R 2 All of them represent groups represented by formula (II).

[0026] Formula (II) P-Sp-L 3 - In the formula, P represents a group represented by any of the formulas (P-1) to (P-3). The formulas (P-1) to (P-3) Indicates the bonding location.

[0027] [Chemical Formula 1]

[0028] Sp represents an alkylene group having 1 to 10 carbon atoms or a single bond. Among them, alkylene groups having 1 to 10 carbon atoms are preferred as Sp, and alkylene groups having 3 to 8 carbon atoms are more preferred. L 3 This indicates -O-, -COO-, -OCO-, or a single bond. Among these, L represents... 3 , preferred -O-. In formula (II) Indicates the bonding location.

[0029] A 1 and A 2 Each of these terms independently represents 1,4-phenylene, 1,4-cyclohexylene, or naphthalene-2,6-dimethylene, which can be substituted with one or more substituents S. A 1 When multiple A exist, they can be the same or different. 2 When multiple instances exist, they can be the same or different. The substituent S represents a fluorine atom, a chlorine atom, a straight-chain alkyl group having 1 to 8 carbon atoms, or a straight-chain alkoxy group having 1 to 8 carbon atoms.

[0030] L 1 and L 2 Each can independently represent -O-, -OCH2-, -CH2O-, -CH2CH2-, -COO-, -OCO-, -COO-CH2CH2-, -OCO-CH2CH2-, -CH2CH2-COO-, -CH2CH2-OCO-, or a single bond. 1 When multiple instances exist, they can be the same or different, L 2 When multiple instances exist, they can be the same or different. Among them, at least one of the following conditions must be met: -A directly bonded to G 1 -L 1 - represents the group represented by formula (V-1), and -L is directly bonded to G. 2 -A 2 - is a group represented by formula (V-2). That is, it satisfies at least one of the following requirements 1 and 2. Requirement 1: Directly bonded to G's -A 1 -L 1 - is the group represented by formula (V-1) Requirement 2: Directly bonded to G's -L 2 -A 2 - is the group represented by formula (V-2). Among them, the preferred type is -A directly bonded to G. 1 -L 1 - is a group represented by formula (V-1) and directly bonded to G's -L 2 -A 2 - represents the group indicated by formula (V-2).

[0031] [Chemical Formula 2]

[0032] 1 indicates the bonding position with G. G represents a group represented by any one of the formulas (G-1) to (G-7). Indicates the bonding location.

[0033] [Chemical Formula 3]

[0034] T represents the group represented by formula (T). Indicates the bonding location. In formulas (G-1) to (G-7), these groups can be substituted by substituents. There are no particular restrictions on the types of substituents. For example, fluorine, chlorine, bromine, iodine, pentafluorothioalkyl, nitro, cyano, isocyano, amino, hydroxyl, mercapto, methylamino, dimethylamino, diethylamino, diisopropylamino, trimethylsilyl, dimethylsilyl, thioisocyano, or straight-chain or branched alkyl groups having 1 to 20 carbon atoms, wherein one -CH2- or two or more non-adjacent -CH2- groups can be independently replaced by -O-, -S-, -CO-, -COO-, -OCO-, -CO-S-, -S-CO-, -O-CO-O-, -CO-NH-, -NHCO-, -CH=CH-COO-, -CH=CH-OCO-, -COO-CH=CH-, -OCO-CH=CH-, -CH=CH-, -CF=CF-, or -C≡C-.

[0035] [Chemical Formula 4]

[0036] W represents a hydrogen atom, or a straight-chain alkyl group having 1 to 12 carbon atoms, wherein one -CH2- or two or more non-adjacent -CH2- atoms in the alkyl group may be independently replaced by -O-. Preferably, W is a straight-chain alkyl group having 1 to 12 carbon atoms. The straight-chain alkyl group preferably has 3 to 9 carbon atoms. The aforementioned straight-chain alkyl groups may have substituents. There are no particular restrictions on the types of substituents, but polymerizable groups are preferred. Furthermore, the type of polymerizable group is not particularly limited in this specification. Functional groups capable of undergoing addition polymerization are preferred, polymerizable olefinic unsaturated groups or cyclic polymerizable groups are more preferred, and (meth)acryloyloxy, vinyl, styrene or allyl are even more preferred.

[0037] Y represents a hydrogen atom, a straight-chain alkyl group having 1 to 20 carbon atoms, or a branched alkyl group having 1 to 20 carbon atoms. Among these, hydrogen atoms are preferred as Y. R 3 This refers to a straight-chain alkyl group or a straight-chain alkoxy group having 1 to 8 carbon atoms, consisting of hydrogen, fluorine, chlorine, and carbon atoms. Among these, R... 3 Hydrogen atoms are preferred. m1 and m2 each independently represent 1 or 2. Among them, 2 is preferred as m1 and m2.

[0038] There is no particular limitation on the content of the compound represented by formula (I) in this composition. It is mostly 50 to 97% by mass relative to the total solid content of this composition. From the viewpoint of further suppressing uneven color tone, it is preferably 85% by mass or less. The compound represented by formula (I) may be used alone or in two or more forms. When using two or more compounds represented by formula (I), it is preferable that their total amount is within the range described above.

[0039] This composition may contain other components besides the compound represented by formula (I) above. The other components are described in detail below.

[0040] (Compounds with positive wavelength dispersibility) This composition may contain compounds with positive wavelength dispersive properties. A compound with positive wavelength dispersibility is a compound whose in-plane retardation (Re) value decreases as the measurement wavelength increases when the in-plane retardation (Re) value of an optical anisotropic layer made by uniformly oriented the compound is measured in the visible light range.

[0041] There is no particular limitation on the birefringence Δn of positive wavelength dispersive compounds at a wavelength of 550 nm, with 0.050 to 0.150 being the most common values. From the viewpoint of further suppressing hue inhomogeneity, 0.050 to 0.100 is preferred. The method for measuring the birefringence Δn of the above-mentioned positive wavelength dispersive compound at a wavelength of 550 nm will be described in detail later. For example, a method can be used to measure the birefringence Δn of a phase difference film obtained by uniformly oriented the compound as the test object, and to use the obtained value as the birefringence Δn of the positive wavelength dispersive compound at a wavelength of 550 nm. Furthermore, as a method for measuring the birefringence Δn of a phase retardation film obtained by uniformly orienting the compound to be measured, the aforementioned method for measuring the birefringence Δn of this phase retardation film can be cited. Furthermore, when a positive wavelength dispersive compound does not exhibit liquid crystal properties, the operation of forming the aforementioned phase difference film using the composition obtained by mixing the compound being measured with other liquid crystal-dispersible compounds and calculating its birefringence Δn can be performed while changing the mixing ratio of the compound being measured with other liquid crystal-dispersible compounds. The birefringence Δn of the compound being measured can then be extrapolated from the multiple measured values ​​obtained.

[0042] As a compound with positive wavelength dispersibility, a rod-shaped liquid crystal compound with positive wavelength dispersibility is preferred. Positive wavelength dispersive rod-shaped liquid crystal compounds preferably have polymerizable groups. The types of polymerizable groups are as described above. Examples of polymerizable rod-shaped liquid crystal compounds include, for example, the compounds described in claim 1 of Japanese Patent Application Publication No. 11-513019 and paragraphs 0026 to 0098 of Japanese Patent Application Publication No. 2005-289980.

[0043] The content of the positive wavelength dispersive compound in this composition is not particularly limited, but is preferably 1 to 50% by mass, more preferably 5 to 20% by mass, relative to the total solid content in this composition. One or more compounds with positive wavelength dispersibility can be used alone. When using two or more compounds with positive wavelength dispersibility, it is preferable that their total amount is within the range described above.

[0044] (Multifunctional monomer) This composition may contain a multifunctional monomer. The multifunctional monomer is a compound that is different from the compound represented by formula (I) above and the compound with positive wavelength dispersibility. By using multifunctional monomers, the birefringence Δn of this phase difference film can be adjusted.

[0045] A polyfunctional monomer is a monomer that has two or more polymerizable groups in one molecule. The types of polymerizable groups are as described above. From the perspective of superior curability, multifunctional free radical polymerizable monomers are preferred, and multifunctional olefinic unsaturated monomers are even more preferred. Examples of polyfunctional olefinic unsaturated monomers include, for example, polyfunctional (meth)acrylates and polyfunctional vinyl ethers, with polyfunctional (meth)acrylates being preferred.

[0046] Examples of polyfunctional (meth)acrylates include, for example, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, propylene glycol dimethacrylate, dipropylene glycol dimethacrylate, tripropylene glycol dimethacrylate, polypropylene glycol dimethacrylate, butanediol dimethacrylate, tetraethylene glycol dimethacrylate, neopentyl glycol dimethacrylate, 3-methyl-1,5-pentanediol dimethacrylate, 1,6-hexanediol dimethacrylate, heptaethylene glycol dimethacrylate, octyl glycol dimethacrylate, nonanediol dimethacrylate, and decanediol dimethacrylate. Ester, dodecanediol di(meth)acrylate, glycerol di(meth)acrylate, pentaerythritol di(meth)acrylate, ethylene glycol diglycidyl ether di(meth)acrylate, diethylene glycol diglycidyl ether di(meth)acrylate, tricyclodecanediethanol di(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tri(meth)acryloyloxyethoxytrimethylolpropane, glycerol polyglycidyl ether poly(meth)acrylate and tris(2-acryloyloxyethyl)isocyanurate.

[0047] There is no particular limitation on the content of the polyfunctional monomers in this composition, but it is preferably 1 to 30% by mass, more preferably 5 to 20% by mass, relative to the total solid content in this composition. A single multifunctional monomer can be used alone, or two or more can be used. When using two or more multifunctional monomers, it is preferable that their total amount is within the range mentioned above.

[0048] (Polyfunctional thiols) This composition may contain a polyfunctional thiol compound. The polyfunctional monomer is the compound represented by formula (I) above, a compound with positive wavelength dispersibility, or a compound different from the polyfunctional monomer. By using a multifunctional thiol compound, the birefringence Δn of this phase difference film can be adjusted.

[0049] Polyfunctional thiols are compounds that have two or more thiol groups in one molecule. Examples of polyfunctional thiols include, for example, 1,3-propanedithiol, 1,4-butanedithiol, 1,6-hexanedithiol, 2,5-hexanedithiol, 1,8-octanedithiol, 1,9-nonanedithiol, 3,7-dithia-1,9-nonanedithiol, 1,4-bis(3-mercaptobutyryloxy)butane, tetraethylene glycol bis(3-mercaptopropionate), dimercaprol, 1,2-bis(mercaptomethyl)benzene, 1,3-bis(mercaptomethyl)benzene, 1,4 -Di(mercaptomethyl)benzene, 1,3-dimercapto-5-methylbenzene, 4,5-dimercapto-1,3,4-thiadiazole, trimethylolpropane tris(3-mercaptobutyrate), trimethylolpropane tris(3-mercaptopropionate), tri-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, trimethylolethane tris(3-mercaptobutyrate), pentaerythritol tetras(3-mercaptobutyrate), pentaerythritol tetras(3-mercaptopropionate), and dipentaerythritol hexas(3-mercaptopropionate).

[0050] The content of polyfunctional thiols in this composition is not particularly limited, but is preferably 1 to 20% by mass, more preferably 2 to 10% by mass, relative to the total solids content in this composition. A single polyfunctional thiol compound may be used alone, or two or more may be used. When using two or more polyfunctional thiol compounds, it is preferable that their total amount is within the range described above.

[0051] (Polymerization initiator) This composition may contain a polymerization initiator. As a polymerization initiator, a photopolymerization initiator is preferred, and a photopolymerization initiator capable of initiating a polymerization reaction by ultraviolet irradiation (e.g., light with a wavelength of 10 to 400 nm) is more preferred. Examples of photopolymerization initiators include acylphosphine compounds, acetophenone compounds, α-aminoketone compounds, benzophenone compounds, benzoin ether compounds, ketal derivative compounds, thioxanone compounds, oxime compounds, hexaarylbiimidazole compounds, trihalomethyl compounds, azo compounds, organic peroxides, diazo compounds, iodonium compounds, sulfonium compounds, azadinium compounds, benzoin ether compounds, ketal derivative compounds, metallocene compounds, and other ononium salts, organoboronium salts, and disulfone compounds. From the viewpoint of further reducing the residual rate of polymerizable groups in the phase difference film, oxime initiators are preferred. Examples of oxime initiators include, for instance, oxime ester compounds.

[0052] The content of polymerization initiator in this composition is not particularly limited, but it is preferably 0.01 to 10% by mass, more preferably 0.1 to 5% by mass, relative to the total mass of polymerizable compounds in this composition. A polymerization initiator can be used alone or in combination with two or more. When using two or more polymerization initiators, it is preferable that their total amount is within the range described above.

[0053] (Leveling agent) This composition may contain a leveling agent. As a leveling agent, fluorinated leveling agents or silicone leveling agents are preferred, and silicone leveling agents are more preferred, based on the high leveling effect relative to the amount added. As a silicon-based leveling agent, a polymeric leveling agent is preferred, and a polymer containing repeating units having a group represented by -Si(R)3 (R represents alkyl, alkenyl, aryl or alkylene aryl).

[0054] The content of leveling agent in this composition is not particularly limited, but is preferably 0.001 to 1.0% by mass, more preferably 0.01 to 0.1% by mass, relative to the total solid content of the composition. A leveling agent can be used alone or in combination with two or more agents. When using two or more leveling agents, it is preferable that their total dosage be within the range described above.

[0055] (solvent) This composition may contain a solvent. Examples of solvents include water and organic solvents. Organic solvents that can dissolve the components incorporated in this composition include, for example, ketone solvents, ester solvents, ether solvents, amide solvents and hydrocarbon solvents.

[0056] The solvent content in this composition is preferably set to a solid component concentration of 0.5 to 50% by mass, more preferably 1 to 35% by mass. One solvent may be used alone, or two or more solvents may be used. When using two or more solvents, it is preferable that their total amount is within the range mentioned above.

[0057] Other components, besides those mentioned above, include orientation control agents, adhesion improvers, and plasticizers.

[0058] <Manufacturing Method of Phase Retardation Film> The method for manufacturing this phase retardation film is not particularly limited as long as it is formed from this composition. For example, a preferred method for manufacturing this phase retardation film is to coat the composition, perform an orientation treatment on the formed coating to orient the polymeric liquid crystal compound in the coating, and then perform a curing treatment. The above method will be explained in detail below. This composition is as described above.

[0059] Examples of substrates to which this composition is applied include substrates having an alignment film. The alignment film may be a photoalignment film. Furthermore, if the surface of the positive C-plate described later has orientation-restricting forces, the positive C-plate can be used as the object to be coated.

[0060] Examples of coating methods for this composition include curtain coating, dip coating, spin coating, printing coating, spray coating, slot coating, roller coating, sliding coating, doctor blade coating, gravure coating, and wire rod coating.

[0061] Orientation processing can be performed by drying the coating at room temperature or by heating the coating. In the case of thermotropic liquid crystal compounds, the liquid crystal phase formed by orientation processing can typically change according to changes in temperature or pressure. In the case of lyotropic liquid crystal compounds, the phase can also change according to the composition ratio of solvents, etc. In addition, the conditions for heating the coating are not particularly limited, but the heating temperature is preferably 50 to 250°C, more preferably 50 to 150°C, and the heating time is preferably 10 seconds to 10 minutes. Furthermore, after heating the coating, it can be cooled as needed before the curing process (light irradiation treatment) described later.

[0062] There are no particular limitations on the method of curing the coating; for example, light irradiation and heat treatment can be mentioned. From the viewpoint of manufacturing suitability, light irradiation is preferred, and ultraviolet irradiation is more preferred. There are no particular restrictions on the irradiation conditions for light treatment, but 50–1000 mJ / cm² is preferred. 2 The amount of radiation. The atmosphere used during light irradiation is not particularly restricted, but a nitrogen atmosphere is preferred.

[0063] <Polarizing plate> The polarizer of the present invention (hereinafter also simply referred to as "this polarizer") includes this phase difference film and a polarizer. The structure of this phase retardation film is as described above. Furthermore, there is no particular limitation on the angle between the in-plane slow axis of this phase difference film and the absorption axis of the polarizer, but from the viewpoint that the polarizer of the present invention is superior as a circular polarizer, it is preferred to be in the range of 45±10° (35 to 55°).

[0064] (Polarizer) A polarizer is any component that can convert natural light into linearly polarized light; for example, an absorption polarizer can be cited. There are no particular restrictions on the type of polarizer; commonly used polarizers can be used, such as iodine-based polarizers, dye-based polarizers utilizing dichroic substances, and polyene-based polarizers. Iodine-based and dye-based polarizers are usually made by adsorbing iodine or dichroic dyes onto polyvinyl alcohol and then stretching it.

[0065] As a polarizer, a polarizer formed by using a composition comprising a dichroic substance and a liquid crystal compound having polymerizable groups is also preferred. There are no particular limitations on dichroic substances. Examples include visible light absorbing substances (dichroic pigments), luminescent substances (fluorescent substances, phosphorescent substances), ultraviolet light absorbing substances, infrared light absorbing substances, nonlinear optical substances, carbon nanotubes, and inorganic substances (such as quantum rods). Previously known dichroic substances (dichroic pigments) can be used.

[0066] There is no particular limitation on the thickness of the polarizer, but from the viewpoint of enabling the polarizer to be thinner, it is preferable to be 40 μm or less, more preferably 25 μm or less. There is no particular limitation on the lower limit, but it is mostly 5 μm or more.

[0067] (Positive C board) The polarizer of the present invention may include a positive C-plate. In the polarizer, the positive C-plate is preferably positioned on the side opposite to the polarizer side of the retardation film. That is, the polarizer, the retardation film, and the positive C-plate are preferably arranged in sequence. This phase difference film can be in direct contact with the positive C plate, or it can be laminated through a sealing layer as described later.

[0068] The definition of a positive C-plate is as described above. There is no particular limitation on the thickness direction delay Rth(550) of the positive C plate at a wavelength of 550nm, but from the viewpoint that the polarizer of the present invention is more superior as a circular polarizer, it is preferably -120 to -10nm, and more preferably -100 to -30nm.

[0069] There are no particular restrictions on the structure of the positive C plate; examples include vertically aligned liquid crystal layers (layers formed by fixing vertically aligned rod-shaped liquid crystal compounds) and polymer films. Furthermore, the vertical orientation of the rod-shaped liquid crystal compound means that the long axis of the rod-shaped liquid crystal compound is parallel to the thickness direction of the positive C-plate. However, strict parallelism is not required; the angle between the long axis of the rod-shaped liquid crystal compound and the thickness direction of the positive C-plate is preferably in the range of 0 ± 20°, and more preferably in the range of 0 ± 10°. Furthermore, the vertically oriented liquid crystal layer is preferably formed by polymerizing a polymeric rod-shaped liquid crystal compound that is fixed in a vertical orientation. As a rod-shaped liquid crystal compound, known compounds can be used.

[0070] There is no particular limitation on the thickness of the positive C plate. From the viewpoint of thinness, it is preferred to be less than 10 μm, and more preferably 0.1 to 5.0 μm. Furthermore, the thickness of the positive C-plate refers to its average thickness. This average thickness is calculated by measuring the thickness at any five or more points on the positive C-plate and taking their arithmetic mean. The thickness can be measured, for example, using a reflective spectrophotometer FE3000.

[0071] (Orientation film) This polarizer may include an alignment film. In particular, this polarizer preferably includes an alignment film disposed adjacent to this retardation film. As an alignment film, a so-called photoalignment film is preferred.

[0072] (Sealed layer) To improve the tightness between components, this polarizer may further include a sealing layer. The adhesive layer is selected from the group consisting of the adhesive layer and the bonding agent layer. The adhesive layer is a layer formed using an adhesive. Examples of adhesives include rubber-based adhesives, acrylic adhesives, silicone adhesives, urethane adhesives, vinyl alkyl ether adhesives, polyvinyl alcohol adhesives, polyvinylpyrrolidone adhesives, polyacrylamide adhesives, and cellulose adhesives, with acrylic adhesives or polyvinyl alcohol adhesives (PVA adhesives) being preferred. The adhesive layer is a layer formed to allow the adhesive to cure. Examples of adhesives include, for example, active energy radiation-curable adhesives and thermosetting adhesives. Examples of active energy radiation-curable adhesives include electron beam-curable adhesives, ultraviolet-curable adhesives, and visible light-curable adhesives, with ultraviolet-curable adhesives being preferred. That is, the adhesive layer is preferably a layer formed by curing an ultraviolet-curable adhesive.

[0073] This polarizer may include other components besides those mentioned above (e.g., polarizer protective film and substrate).

[0074] <Application> This polarizer is suitable for a variety of applications. In particular, it is preferably suitable for display devices. More specifically, this polarizer with the above structure is preferably used as an anti-reflective film for display devices such as liquid crystal displays (LCDs), plasma display panels (PDPs), electroluminescent displays (ELDs), and cathode ray tube displays (CRTs). The display device of the present invention includes a display element and the polarizer described above. When this polarizer is applied to a display device, a method can be given as follows: the phase difference film in this polarizer is set on the display element side and the display element and the polarizer are attached together. There are no particular limitations on display elements; examples include organic electroluminescent display elements and liquid crystal display elements. Example

[0075] The following examples and comparative examples further illustrate the features of the present invention. The materials, amounts, proportions, processing contents, and processing steps shown in the following examples can be appropriately modified without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as limiting by the specific examples shown below.

[0076] <Example 1> (Preparation of cellulose acylate membrane (1)) The following composition was added to a mixing vessel and stirred, then heated at 90°C for 10 minutes. A concentrated solution was then prepared by filtering the obtained composition through filter paper with an average pore size of 34 μm and a sintered metal filter with an average pore size of 10 μm. The solids concentration of the concentrated solution was 23.5% by mass, and the solvent was dichloromethane / methanol / butanol in a mass ratio of 81 / 18 / 1.

[0077] ―――――――――――――――――――――――――――――――― Cellulose acylate concentrate ―――――――――――――――――――――――――――――――― Cellulose acylated (acetyl substitution degree 2.86, viscosity-average polymerization degree 310) 100 portions Sugar ester compound 1 (shown by formula (S4) below) 6.0 parts by mass Sugar ester compound 2 (shown by formula (S5) below) 2.0 parts by mass Silica particle dispersion (AEROSIL R972, manufactured by NIPPON AEROSIL CO.,LTD.) 0.1 parts by weight Solvents (dichloromethane / methanol / butanol) ――――――――――――――――――――――――――――――――

[0078] [Chemical Formula 5]

[0079] [Chemical Formula 6]

[0080] The concentrated liquid prepared above was cast using a roller film casting machine. The concentrated liquid was cast from the die head to contact a metal support cooled to 0°C, and then the resulting continuous web (film) was peeled off. The roller was made of SUS.

[0081] After the continuous film strip obtained by casting was peeled off from the roller, it was dried for 20 minutes in a tenter frame at 30-40°C using a tenter frame that clamps both ends of the film. Then, while the continuous film strip was being conveyed by rollers, it was post-dried by zone heating. After knurling the obtained continuous film strip, it was wound up to produce a cellulose acylated film with a thickness of 40 μm (1). The in-plane retardation of the cellulose acylated membrane (1) at a wavelength of 550 nm is 0 nm, and the thickness retardation at a wavelength of 550 nm is 23 nm.

[0082] (Formation of photo-aligned film PA1) The photo-alignment film forming composition PA-1 (described later) was continuously coated onto the cellulose acylated film (1) using a wire rod. The support with the coated film was dried with warm air at 140°C for 120 seconds, and then the coating was irradiated with polarized ultraviolet light (10 mJ / cm²). 2 Using an ultra-high pressure mercury lamp, a photo-aligned film PA1 was formed, resulting in a TAC (triacetyl cellulose) membrane with a photo-aligned film. The thickness of the photo-aligned film PA1 was 0.7 μm. ―――――――――――――――――――――――――――――――― PA-1 composition for photo-aligned film formation ―――――――――――――――――――――――――――――――― • 100.0 parts by weight of the following polymer PA-1 • 5.0 parts by weight of the following acid-producing agent TAG-1 0.6 parts by weight of diisopropylethylamine 16.5 parts by weight of isopropanol ·Butyl acetate 1072.0 parts by weight · 268.0 parts by weight of methyl ethyl ketone ――――――――――――――――――――――――――――――――

[0083] Polymer PA-1 (weight average molecular weight: 45000) (In the following formulas, the values ​​recorded in each repeating unit represent the content (mass%) of each repeating unit relative to all repeating units.)

[0084] [Chemical Formula 7]

[0085] Acid-producing agent TAG-1

[0086] [Chemical Formula 8]

[0087] (Fabrication of phase retardation film A1) The obtained elongated optical alignment film PA1 was irradiated with UV light (ultra-high pressure mercury lamp; UL750; manufactured by HOYA Corporation) that had passed through a wire grid polarizer, producing a light intensity of 7.9 mJ / cm². 2 (Wavelength: 313nm) Afterwards, a phase retardation film forming composition A1, comprising a rod-shaped compound with the following composition, is coated onto the photoalignment film PA1 using a die coater. The mixture is heated to 130°C with warm air, then cooled to 120°C, and irradiated with ultraviolet light (300mJ / cm²) under a nitrogen atmosphere (oxygen concentration less than 100ppm) using an ultra-high pressure mercury lamp. 2 This fixes the orientation, forming the phase difference film A1. The phase retardation film A1 has a thickness of 2.1 μm and a Re(550) of 138 nm at a wavelength of 550 nm. If the width direction of the film is set to 0° (and the length direction is set to 90°), then the in-plane slow axis direction (the orientation axis angle of the compound) is 45°. Furthermore, Re(450) / Re(550) is 0.92.

[0088] ―――――――――――――――――――――――――――――――― Composition A1 for phase retardation film formation ―――――――――――――――――――――――――――――――― 85.0 parts by mass of the following compound I-1 The following rod-shaped compound RLC-1, 15.0 parts by weight Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The following leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0089] Compound I-1

[0090] [Chemical Formula 9]

[0091] Rod-shaped compound RLC-1 (hereinafter, a mixture of compounds. Numerical values ​​represent mass ratios. It is a rod-shaped compound with positive wavelength dispersivity. The birefringence at 550 nm is Δn(550) = 0.13)

[0092] [Chemical Formula 10]

[0093] Leveling agent L-1 (weight average molecular weight: 20000. The values ​​listed for each repeating unit in the main chain indicate the content (mass ratio) of each repeating unit relative to all repeating units. The values ​​listed for each repeating unit in the side chain indicate the number of repeating units.)

[0094] [Chemical Formula 11]

[0095] Through the above steps, a long strip-shaped laminated film A1 with a light-oriented film PA1 and a phase difference film A1 stacked on a cellulose acylated film (1) was prepared.

[0096] (Making of C1 on the positive C board) The positive C-plate forming composition C1 with the following composition was coated onto the cellulose acylated film (1) described above, and the resulting coating was heated at 60°C for 60 seconds. Afterwards, it was subjected to a 70 mW / cm² heat treatment in air. 2 An air-cooled metal halide lamp (manufactured by EYEGRAPHICS Co., Ltd.) provides 300 mJ / cm² irradiation. 2 The ultraviolet light is used to fix its orientation state, thereby making the liquid crystal compound vertically oriented, forming a positive C plate with a thickness of 0.5 μm and Rth(550) = -60 nm.

[0097] ―――――――――――――――――――――――――――――――― Composition C1 for forming positive C plates ―――――――――――――――――――――――――――――――― 100 parts by weight of the above rod-shaped compound RLC-1 Polymerizable monomer UA-601I (manufactured by Kyoeisha Chemical Co., Ltd.) 5.0 parts by weight Photopolymerization initiator IrgacureOXE01 (manufactured by BASF) 4.0 parts by weight The following leveling agent SC-1, 0.4 parts by weight The following vertically oriented liquid crystal compound alignment agent S01: 1.2 parts by weight The following polymer M is 1.14 parts by weight 494.9 parts by weight of methyl isobutyl ketone 95.0 parts by weight of ethyl propionate 43.3 parts by weight of 2-Butanone ――――――――――――――――――――――――――――――――

[0098] Leveling agent SC-1 (weight average molecular weight: 25000. The values ​​listed in each repeating unit indicate the content (mass ratio) of each repeating unit relative to all repeating units.)

[0099] [Chemical Formula 12]

[0100] Vertically oriented liquid crystal compound alignment agent S01

[0101] [Chemical Formula 13]

[0102] Polymer M (weight average molecular weight: 60,000. The values ​​recorded in each repeating unit indicate the content (mass ratio) of each repeating unit relative to all repeating units.)

[0103] [Chemical Formula 14]

[0104] (Fabrication of polarizers and image display devices) [Fabrication of polarizer 1 with protective film] The surface of the support for the cellulose triacetate membrane TJ25 (manufactured by FUJIFILM Corporation: 25 μm thickness) was subjected to alkaline saponification treatment. Specifically, the support was immersed in a 1.5 equivalent sodium hydroxide aqueous solution at 55°C for 2 minutes, then cleaned in a water bath at room temperature, and further neutralized with 0.1 equivalent sulfuric acid at 30°C. After neutralization, the support was cleaned in a water bath at room temperature and then dried with warm air at 100°C to obtain the polarizer protective film. A roll of polyvinyl alcohol film was stretched in an aqueous iodine solution along the MD (Machine Direction) direction and dried to obtain a polarizer 1 with a thickness of 14 μm. The protective film of the polarizer is attached to one surface of the polarizer 1 using PVA adhesive, thereby creating a polarizer 1 with a protective film.

[0105] [Preparation of Ultraviolet (UV) Adhesive 1] A UV adhesive 1 with the following composition was prepared. ―――――――――――――――――――――――――――――――― UV adhesive 1 ―――――――――――――――――――――――――――――――― CEL2021P (manufactured by Daicel Corporation) 70 parts by weight 20 parts by weight of 1,4-Butanediol diglycidyl ether 10 parts by weight of 2-ethylhexyl glycidyl ether CPI-100P 2.25 parts by weight ――――――――――――――――――――――――――――――――

[0106] CPI-100P

[0107] [Chemical Formula 15]

[0108] [Fabrication of polarizer P1] The obtained elongated phase retardation film A1 and the surface of the positive C plate C1 were continuously subjected to corona treatment (treatment rate 100 W / min / m). 2 Next, using the aforementioned UV adhesive 1, the corona-treated phase retardation film A1 and the positive C-plate C1 were bonded together, and irradiated from the positive C-plate C1 side with 500 mJ / cm². 2 The UV light is used to cure the UV adhesive, thereby obtaining a laminate. Then, the photo-alignment film PA1 and the cellulose acylate film (1) are removed from the laminate, thereby obtaining a laminate F1 consisting of phase difference film A1 / UV adhesive / positive C plate C1 / cellulose acylate film (1) stacked sequentially. Using pressure-sensitive adhesive SK-2057 (manufactured by Soken Chemical & Engineering Co., Ltd.), the surface of the polarizer side of the polarizer 1 with protective film prepared above was bonded to the phase retardation film A1 side of the above-mentioned laminate F1, and the cellulose acylate film (1) on the positive C plate C1 side was removed, thereby completing the circular polarizer P1. At this time, the angle between the absorption axis of the polarizer included in the polarizer 1 with protective film and the slow axis of the phase retardation film A1 is 45°.

[0109] <Example 2> The phase retardation film forming composition A1 of Example 1 was changed to the phase retardation film forming composition A2 described below, and the thickness of the phase retardation film was changed. Otherwise, the phase retardation film A2, the laminated film A2, the laminate F2 and the circular polarizer P2 were prepared using the same method as in Example 1.

[0110] ―――――――――――――――――――――――――――――――― Composition A2 for phase retardation film formation ―――――――――――――――――――――――――――――――― 65.0 parts by mass of the above compound I-1 The following rod-shaped compound RLC-2, 35.0 parts by weight Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0111] Rod-shaped compound RLC-2 (belongs to the category of rod-shaped compounds with positive wavelength dispersivity. Birefringence at 550 nm Δn(550) = 0.056, an estimate based on extrapolation from data of a mixture with RLC-1). Me represents methyl.

[0112] [Chemical Formula 16]

[0113] <Example 3> The phase retardation film forming composition A1 of Example 1 was changed to the phase retardation film forming composition A3 described below, and the thickness of the phase retardation film was changed. Otherwise, the phase retardation film A3, the laminated film A3, the laminate F3 and the circular polarizer P3 were prepared using the same method as in Example 1.

[0114] ―――――――――――――――――――――――――――――――― Composition A3 for phase retardation film formation ―――――――――――――――――――――――――――――――― 65.0 parts by mass of the above compound I-1 35.0 parts by weight of the above rod-shaped compound RLC-2 Multifunctional acrylate dipentaerythritol hexaacrylate (DPHA) 15.0 parts by weight Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0115] <Example 4> The phase retardation film forming composition A1 of Example 1 was changed to the phase retardation film forming composition A4 described below, and the thickness of the phase retardation film was changed. Otherwise, the phase retardation film A4, the laminated film A4, the laminate F4 and the circular polarizer P4 were prepared using the same method as in Example 1.

[0116] ―――――――――――――――――――――――――――――――― Composition A4 for phase retardation film formation ―――――――――――――――――――――――――――――――― 65.0 parts by mass of the above compound I-1 35.0 parts by weight of the above rod-shaped compound RLC-2 Multifunctional thiols KARENZ MT PE1 (manufactured by Karenz) 5.0 parts by weight Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0117] <Example 5> The phase retardation film forming composition A1 of Example 1 was changed to the phase retardation film forming composition A5, and the thickness of the phase retardation film was changed. Otherwise, the phase retardation film A5, the laminated film A5, the laminate F5 and the circular polarizer P5 were prepared using the same method as in Example 1.

[0118] ―――――――――――――――――――――――――――――――― Composition A5 for phase difference film formation ―――――――――――――――――――――――――――――――― 90.0 parts by mass of the above compound I-1 10.0 parts by weight of the above rod-shaped compound RLC-2 Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0119] <Example 6> The phase retardation film forming composition A1 of Example 1 was changed to the phase retardation film forming composition A6 described below, and the thickness of the phase retardation film was changed. Otherwise, the phase retardation film A6, the laminated film A6, the laminate F6 and the circular polarizer P6 were prepared using the same method as in Example 1.

[0120] ―――――――――――――――――――――――――――――――― Composition A6 for phase retardation film formation ―――――――――――――――――――――――――――――――― 90.0 parts by mass of the above compound I-1 10.0 parts by weight of the above rod-shaped compound RLC-2 Multifunctional thiols Karenz MT PE1 (manufactured by Karenz) 5.0 parts by weight Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0121] <Example 7> The phase retardation film forming composition A1 of Example 1 was changed to the phase retardation film forming composition A7 described below, and the thickness of the phase retardation film was changed. Otherwise, the phase retardation film A7, the laminated film A7, the laminate F7 and the circular polarizer P7 were fabricated using the same method as in Example 1.

[0122] ―――――――――――――――――――――――――――――――― Composition A7 for phase retardation film formation ―――――――――――――――――――――――――――――――― 90.0 parts by mass of the above compound I-1 The following rod-shaped compound RLC-3, 10.0 parts by weight Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0123] The rod-shaped compound RLC-3 (belongs to the category of rod-shaped compounds with positive wavelength dispersivity. The birefringence at a wavelength of 550 nm is Δn(550) = 0.10)

[0124] [Chemical Formula 17]

[0125] <Example 8> The phase retardation film forming composition A1 of Example 1 was changed to the phase retardation film forming composition A8 described below, and the thickness of the phase retardation film was changed. Otherwise, the phase retardation film A8, the laminated film A8, the laminate F8 and the circular polarizer P8 were fabricated using the same method as in Example 1.

[0126] ―――――――――――――――――――――――――――――――― Composition A8 for phase retardation film formation ―――――――――――――――――――――――――――――――― 100.0 parts by mass of the above compound I-2 Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0127] Compound I-2 (tBu represents tert-butyl)

[0128] [Chemical Formula 18]

[0129] <Example 9> The phase retardation film forming composition A1 of Example 1 was changed to the phase retardation film forming composition A9 described below, and the thickness of the phase retardation film was changed. Otherwise, the phase retardation film A9, the laminated film A9, the laminate F9 and the circular polarizer P9 were fabricated using the same method as in Example 1.

[0130] ―――――――――――――――――――――――――――――――― Composition A9 for phase retardation film formation ―――――――――――――――――――――――――――――――― 50.0 parts by mass of the above compound I-1 50.0 parts by mass of the above compound I-2 Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0131] <Example 10> The phase retardation film forming composition A1 of Example 1 was changed to the phase retardation film forming composition A10 described below, and the thickness of the phase retardation film was changed. Otherwise, the phase retardation film A10, the laminated film A10, the laminate F10 and the circular polarizer P10 were fabricated using the same method as in Example 1.

[0132] ―――――――――――――――――――――――――――――――― Composition A10 for phase retardation film formation ―――――――――――――――――――――――――――――――― The following compound I-3, 45.0 parts by weight The following compound I-4, 45.0 parts by mass 10.0 parts by weight of the above rod-shaped compound RLC-2 Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0133] Compound I-3

[0134] [Chemical Formula 19]

[0135] Compound I-4 (tBu represents tert-butyl)

[0136] [Chemical Formula 20]

[0137] <Example 11> The phase retardation film forming composition A1 of Example 1 was changed to the following phase retardation film forming composition A11, and the thickness of the phase retardation film was changed. Otherwise, the phase retardation film A11, the laminated film A11, the laminate F11 and the circular polarizer P11 were fabricated using the same method as in Example 1.

[0138] ―――――――――――――――――――――――――――――――― Composition A11 for phase retardation film formation ―――――――――――――――――――――――――――――――― 90.0 parts by weight of the following compound I-5 10.0 parts by weight of the above rod-shaped compound RLC-2 Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0139] Compound I-5

[0140] [Chemical Formula 21]

[0141] <Comparative Example 1> When UV light (ultra-high pressure mercury lamp; UL750; manufactured by HOYACorporation) passing through a wire grid polarizer is irradiated onto the aforementioned photoalignment film PA1, the light concentration is 7.9 mJ / cm². 2 (Wavelength: 313nm) Afterwards, a phase retardation film forming composition CA1, comprising a rod-shaped compound with the following composition, is coated onto the photoalignment film PA1 using a die coater. The coating is then heated to 130°C with warm air, cooled to 80°C, and subjected to ultraviolet irradiation (300mJ / cm²) under atmospheric conditions using an ultra-high pressure mercury lamp. 2 This fixes the orientation, forming a phase retardation film CA1. The phase retardation film A1 of Example 1 was replaced with a phase retardation film CA1. Otherwise, a laminated film CA1, a laminated body CF1, and a circular polarizer CP1 were fabricated using the same method as in Example 1.

[0142] ―――――――――――――――――――――――――――――――― Composition CA1 for phase retardation film formation ―――――――――――――――――――――――――――――――― 95.0 parts by mass of the above compound I-1 5.0 parts by weight of the above-mentioned rod-shaped liquid crystal compound RLC-1 Photopolymerization initiator IRGACURE-907 (manufactured by BASF) 5.0 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0143] <Comparative Example 2> The phase retardation film forming composition CA1 of Comparative Example 1 was changed to the phase retardation film forming composition CA2, and the thickness of the phase retardation film was changed. Otherwise, the phase retardation film CA2, the laminated film CA2, the laminated body CF2 and the circular polarizer CP2 were prepared using the same method as Comparative Example 1.

[0144] ―――――――――――――――――――――――――――――――― Composition CA2 for phase retardation film formation ―――――――――――――――――――――――――――――――― 85.0 parts by mass of the above compound I-1 15.0 parts by weight of the above-mentioned rod-shaped liquid crystal compound RLC-1 Photopolymerization initiator IRGACURE 907 (manufactured by BASF) 5.0 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0145] <Comparative Example 3> The phase retardation film forming composition CA1 of Comparative Example 1 was changed to the phase retardation film forming composition CA3, and the temperature during ultraviolet irradiation was changed. Otherwise, the phase retardation film CA3, the laminated film CA3, the laminated body CF3 and the circular polarizer CP3 were prepared using the same method as Comparative Example 1.

[0146] ―――――――――――――――――――――――――――――――― Composition CA3 for phase retardation film formation ―――――――――――――――――――――――――――――――― 100.0 parts by mass of the above compound I-1 Photopolymerization initiator OXE-03 (manufactured by BASF Japan Ltd.) 4.0 parts by weight Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 5.0 parts by weight The above leveling agent L-1, 0.1 parts by weight Antioxidant BHT (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.9 parts by weight 60.0 parts by weight of methyl ethyl ketone Cyclopentanone 240.0 parts by weight ――――――――――――――――――――――――――――――――

[0147] <Comparative Example 4> The phase retardation film forming composition A1 of Example 1 was changed to the phase retardation film forming composition CA3, and the thickness of the phase retardation film was changed. Otherwise, the phase retardation film CA4, the laminated film CA4, the laminated body CF4 and the circular polarizer CP4 were prepared using the same method as in Example 1.

[0148] ―――――――――――――――――――――――――――――――― Composition CA4 for phase retardation film formation ―――――――――――――――――――――――――――――――― 90.0 parts by mass of the above compound I-1 10.0 parts by weight of the above rod-shaped compound RLC-2 Multifunctional acrylate dipentaerythritol hexaacrylate (DPHA) 15.0 parts by weight Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0149] <Evaluation> (Measurement of the thickness of the phase difference layer) The thickness d of the phase retardation layer was measured using a reflective spectrophotometer FE3000 (manufactured by Otsuka Electronics Co., Ltd.).

[0150] (Measurement of optical properties) The in-plane retardation, thickness retardation, and birefringence Δn were determined using the methods described above.

[0151] (Determination of birefringence Δn of compounds with positive wavelength dispersivity (Part 1)) UV light (ultra-high pressure mercury lamp; UL750; manufactured by HOYA Corporation) passing through a wire grid polarizer was irradiated onto the elongated photoalignment film PA1 described in Example 1, producing a light intensity of 7.9 mJ / cm². 2 (Wavelength: 313nm) Afterwards, the following composition 1 was coated onto the photoalignment film PA1 using a rod coater. After heating to 80°C with warm air, it was irradiated with ultraviolet light (300mJ / cm²) under a nitrogen atmosphere (oxygen concentration less than 100ppm) using an ultra-high pressure mercury lamp. 2 This fixes the orientation, forming a film 1 with a thickness of 1.0 μm. ―――――――――――――――――――――――――――――――― Composition 1 ―――――――――――――――――――――――――――――――― 100.0 parts by weight of the above rod-shaped compound RLC-1 Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The above leveling agent L-1, 0.1 parts by weight Cyclopentanone 317.0 parts by weight ――――――――――――――――――――――――――――――――

[0152] The Re(550) of film 1 at a wavelength of 550 nm is 130 nm, and the Δn of the rod-shaped compound RLC-1 is calculated to be 0.13.

[0153] (Determination of birefringence Δn of compounds with positive wavelength dispersivity (Part 2)) The rod-shaped compound RLC-1 in the above composition 1 was replaced with rod-shaped compound RLC-1 and rod-shaped compound RLC-2 or rod-shaped compound RLC-3 as listed in Table 1 below, and films 2 to 4 were prepared. The Δn of rod-shaped compound RLC-2 and rod-shaped compound RLC-3 was calculated to be 0.056 and 0.10 respectively by extrapolation.

[0154] [Table 1]

[0155] (Evaluation of reflectivity) The SAMSUNG Co., Ltd.-manufactured GALAXY S4, which is equipped with an organic EL panel (organic EL display element), was disassembled. The touch panel with a circular polarizer was peeled off from the organic EL display device, and then the circular polarizer was peeled off from the touch panel, separating the organic EL display element, the touch panel, and the circular polarizer. Next, the separated touch panel was re-attached to the organic EL display element. Then, the circular polarizers P1 to P11 and CP1 to CP4, which were prepared above, were attached to the touch panel with the positive C-side as the panel side, using adhesive SK2057 (manufactured by Soken Chemical & Engineering Co., Ltd.), thereby fabricating the organic EL display device. The fabricated organic EL display device was set to a black display state, and the Y value of the display system was measured using a spectrophotometer (manufactured by KonicaMinolta, Inc.) under the conditions of a 10° viewing angle and a D65 light source. The system was then evaluated according to the following criteria. Preferred values ​​are A to C. A: Y - Y0 ≤ 0.2 B: 0.2 < Y - Y0 ≤ 0.3 C: 0.3 < Y - Y0 ≤ 0.5 D: 0.5 < Y - Y0 Wherein, Y0 is the Y value of the reference sample on which the above-mentioned polarizer 1 with protective film is attached to black PET (Lumirror #75-X30, manufactured by TORAYINDUSTRIES, INC.).

[0156] (Wind Spot's evaluation) The circular polarizers P1 to P11 and CP1 to CP4 prepared in Examples 1 to 11 and Comparative Examples 1 to 4 were attached to an aluminum substrate, and the brightness non-uniformity in the MD (machine direction) or tilt direction caused by the phase retardation films A1 to A11 and CA1 to CA4 with a length of more than 10 cm and a width of 1 to 5 cm was evaluated according to the following criteria. A: No inhomogeneity was observed across the entire surface of the polarizer. B: Slight unevenness can be visually observed on the polarizer. C: Obvious unevenness can be visually identified on the polarizer.

[0157] (Evaluation of striped unevenness) The circular polarizers P1 to P11 and CP1 to CP4 prepared in Examples 1 to 11 and Comparative Examples 1 to 4 were cut to a size of 1.3m in width and 1.5m in length, and were attached to an aluminum substrate. The non-uniformity of stripes with a thickness of less than 5mm in the MD direction caused by the phase retardation films A1 to A11 and CA1 to CA4 was evaluated according to the following criteria. A: No striped unevenness was visually discernible on the polarizer. B: A stripe-like unevenness can be visually identified on the polarizer. C: More than two stripe-like unevenness can be visually identified on the polarizer.

[0158] (Evaluation of uneven color tone when displaying black) The samples exhibiting mottled and striped unevenness were evaluated using the above method. The most pronounced unevenness was selected, and a polarizer and an organic EL display device were fabricated using the same method. The organic EL display device was observed under a fluorescent lamp with an attached diffuser in a black display state, and the tonal unevenness was evaluated according to the following criteria. Preferred options are A to C. A: Overall uniformity and no unevenness in tone was observed. B: Upon closer inspection, the color tone is not uniform, but overall it is roughly uniform. C: Slight unevenness in tone observed D: Uneven tonal distribution observed to an unacceptable degree.

[0159] (Durability) Regarding the laminated films A1-A11 and CA1-CA4 prepared in Examples 1-11 and Comparative Examples 1-4, the liquid crystal layer side was set as the glass side and bonded to the glass plate by adhesive, and the cellulose acylate film (1) and the photoalignment film PA1 were removed. The durability of the in-plane retardation value was evaluated using an Axo Scan (0PMF-1, manufactured by Axometrics) with the following indicators. In addition, the test conditions are shown in Table 1 below, and the test was conducted by placing the product in a dry environment at 95°C for 500 hours. A: The change in the post-experiment value relative to the initial phase difference is less than 1% of the initial value. B: The change in the post-experiment value relative to the initial phase difference is greater than 1% and less than 3% of the initial value. C: The change in the post-experiment value relative to the initial phase difference is greater than 3% and less than 10% of the initial value. D: The change in the post-experiment value relative to the initial phase difference is more than 10% of the initial value.

[0160] (Residual rate (determination of the residual rate of polymeric groups)) The phase refraction films A1–A11 and CA1–CA4 were measured relative to the air interface side (plane A) on the plane perpendicular to the thickness direction using a Nicolet 6700 Fourier transform infrared (FT-IR) spectrophotometer (Thermo Fisher Scientific). The residual rate of the (meth)acryloyl group was calculated based on the peak area originating from the C=C group in the obtained spectra. The residual rate was calculated using the absorbance of the liquid crystal component, which remained unchanged before and after the reaction, at 1508 cm⁻¹. -1 Using the area as a benchmark, the peak area of ​​the cured phase retardation film and the absorption originating from the C=C group of the uncured phase retardation film were calculated. -1 The ratio of the area of ​​the peaks. Then, an adhesive was bonded to surface A, and a cyclic olefin polymer (COP) film with a corona-treated surface was pressed onto the adhesive. The cellulose acylate film (1) and the photo-alignment film PA1 were then removed, thereby obtaining a laminate consisting of a COP, an adhesive layer, and a retardation film in sequence. The surface (surface B) of the retardation film on the alignment film side was also measured in the same manner, and the residual rate was calculated. The average of the residual rates of surface A and surface B was taken as the residual rate of the polymeric groups in the retardation film, and it was evaluated according to the following criteria. A: The residual rate of polymeric groups in the phase retardation film is less than 30%. B: The residual rate of polymeric groups in the phase retardation film exceeds 30%.

[0161] The evaluations of Examples 1-11 and Comparative Examples 1-4 are summarized in Tables 2 and 3 below. The “Additive 1” column indicates the type of rod-shaped compound with positive wavelength dispersibility contained in the composition. The “Additive 2” column indicates the polyfunctional monomers or polyfunctional thiols contained in the composition. The “Thickness (μm)” column indicates the thickness (μm) of the phase retardation layer. The “Re(550)(nm)” column indicates the in-plane delay of the phase retardation layer at a wavelength of 550nm. The “Re(450) / Re(550)” column represents the ratio of the in-plane delay Re(450) of the phase retardation layer at a wavelength of 450 nm to the in-plane delay Re(550) at a wavelength of 550 nm. The “Δn(550)” column indicates the birefringence Δn of the phase difference film at a wavelength of 550nm.

[0162] [Table 2]

[0163] [Table 3]

[0164] The results of Examples 1 to 11 show that when the birefringence Δn at 550 nm is in the range of 0.040 or higher and 0.070 or lower, the results of reflectivity and color tone uniformity are both good. The uneven color tone is caused by the unevenness of the phase retardation film, such as the wind spots or stripes. The higher the birefringence Δn, the better the wind pattern results. This is believed to be because when the birefringence Δn is small, the required film thickness to reveal the target phase difference increases, thus increasing the wet coating amount, requiring more drying time, and making it more susceptible to wind influence. On the other hand, a lower birefringence Δn results in a better outcome for stripe-like non-uniformity. This is believed to be because reducing the interaction between liquid crystal compounds suppresses the formation of crystals in the coated area, which is the cause of stripe-like non-uniformity. Furthermore, due to the increased wet coating amount, the shape of the beads in the coated area is less affected by crystals. As shown in the table above, by mixing rod-shaped compounds with positive wavelength dispersibility, the birefringence Δn can be controlled, thus improving hue inhomogeneity. On the other hand, by mixing rod-shaped compounds with positive wavelength dispersibility, the dispersibility Re(450) / Re(550) increases, and therefore the reflectance tends to increase. As shown in Example 5, by mixing rod-shaped compounds with positive wavelength dispersibility and low birefringence Δn, the increase in reflectance is suppressed, and hue inhomogeneity is improved (Examples 2-7, 10, 11). Furthermore, a comparison of Examples 2 and 5 confirmed that when the content of the compound represented by Formula (1) is less than 85% by mass relative to the total solid content in the composition, color unevenness is further suppressed. Furthermore, a comparison of Examples 1, 2, and 7 confirmed that when the birefringence Δn of the positive wavelength dispersive rod-shaped liquid crystal compound at a wavelength of 550 nm is 0.050 to 0.100, color inhomogeneity is further suppressed. Furthermore, a comparison of Examples 1 to 11 confirmed that when Re(450) / Re(550) is 0.93 or less (preferably 0.87 or less), the reflectivity is further reduced. Furthermore, a comparison of Examples 1 to 11 confirmed that when the birefringence Δn of the phase retardation film is 0.050 to 0.058, the color inhomogeneity is further suppressed. Furthermore, a comparison between Examples 1-11 and Comparative Examples 1-3 confirmed that when the residual rate of polymeric groups is 30% or less, the durability is excellent.

[0165] <Example 12> (Formation of photo-aligned film PA2) The photo-alignment film forming composition PA-2 (described later) was continuously coated onto the cellulose acylated film (1) using a wire rod. The support with the coated film was dried with warm air at 140°C for 120 seconds, and then the coating was irradiated with polarized ultraviolet light (10 mJ / cm²). 2 A photo-aligned film PA2 was formed using an ultra-high pressure mercury lamp, resulting in a TAC (triacetyl cellulose) membrane with a photo-aligned film. The thickness of the photo-aligned film PA2 was 0.25 μm. ―――――――――――――――――――――――――――――――― PA-2 composition for photo-aligned film formation ―――――――――――――――――――――――――――――――― • 100.00 parts by weight of the following polymer PA-1 • 8.25 parts by weight of the following acid-producing agent PAG-1 0.6 parts by weight of diisopropylethylamine ·Xylene 1126.60 parts by weight 125.18 parts by weight of methyl isobutyl ketone ――――――――――――――――――――――――――――――――

[0166] Polymer PA-2 (where the value recorded in each repeating unit represents the content (mass%) of each repeating unit relative to all repeating units. Weight-average molecular weight 60,000)

[0167] [Chemical Formula 22]

[0168] Acid-producing agent PAG-1

[0169] [Chemical Formula 23]

[0170] (Fabrication of phase retardation film A12) UV light (ultra-high pressure mercury lamp; UL750; manufactured by HOYA Corporation) passing through a wire grid polarizer was irradiated onto the obtained elongated photo-alignment film PA2. The light intensity was 7.9 mJ / cm². 2 (Wavelength: 313nm) Afterwards, the above-mentioned phase retardation film forming composition A5 is coated on the photoalignment film PA2 using a die coater. After heating to 130°C with warm air and cooling to 120°C, ultraviolet light (300mJ / cm²) is applied using an ultra-high pressure mercury lamp in a nitrogen atmosphere (oxygen concentration less than 100ppm). 2This fixes the orientation, forming the phase retardation film A12. In the phase retardation film A12, Re(550) = 138 nm, Re(450) / Re(550) = 0.86, and birefringence Δn = 0.046.

[0171] (Fabrication of polarizer P12) The obtained elongated phase retardation film A12 and the surface of the aforementioned positive C plate C1 were continuously subjected to corona treatment (treatment rate 100 W / min / m). 2 Next, the phase retardation film A12, which had undergone corona treatment, and the positive C-plate C1 were bonded together using the aforementioned UV adhesive 1, and irradiated from the positive C-plate C1 side with 500 mJ / cm². 2 The UV adhesive was cured by ultraviolet light to obtain a laminate. Then, the cellulose acylate film (1) on the phase retardation film A12 side was removed to obtain a laminate F12 consisting of photo-alignment film PA2 / phase retardation film A12 / UV adhesive / positive C plate C1 / cellulose acylate film (1) stacked in sequence. Using pressure-sensitive adhesive SK-2057 (manufactured by Soken Chemical & Engineering Co., Ltd.), the polarizer side surface of the polarizer 1 with protective film prepared above was bonded to the optical alignment film PA1 side of the aforementioned laminated body F12 with optical film. The cellulose acylate film (1) on the C1 side of the positive C plate was removed, thereby completing the circular polarizer P12. At this time, the angle between the absorption axis of the polarizer included in the polarizer 1 with protective film and the slow axis of the phase difference film A12 is 45°. Organic EL display devices were fabricated using the above method, and reflectivity and color uniformity were evaluated. The results showed that reflectivity was A and color uniformity was B, both of which performed well.

[0172] <Example 13> (Making C2 of the positive C board) Using a die-coating machine, the following positive C-plate forming composition C2 was coated onto the cellulose acylate membrane (1) to form a composition layer. The membrane with the composition layer formed was heated at 60°C for 1 minute with warm air, and while being purged with nitrogen to achieve an oxygen concentration of less than 100 ppm by volume, it was irradiated with a 365nm UV-LED at an irradiation dose of 100mJ / cm². 2 The coating was then subjected to ultraviolet light. The resulting coating was then annealed for 1 minute at 120°C with warm air, thus forming a positive C-plate C2. The positive C-plate C2 has a film thickness of 0.6 μm, an in-plane retardation Re of 0 nm at 550 nm, and a thickness retardation Rth of -70 nm at 550 nm. The average tilt angle of the long axis of the rod-shaped liquid crystal compound relative to the film surface is 90°, confirming a perpendicular orientation relative to the film surface.

[0173] ―――――――――――――――――――――――――――――――― Composition C2 for forming positive C plates ―――――――――――――――――――――――――――――――― 100 parts by weight of the above-mentioned rod-shaped liquid crystal compound RLC-1 Polymerizable monomer (A-400, manufactured by SHIN-NAKAMURA CHEMICAL CO, LTD.) 4.2 parts by weight The following polymerization initiator S-1 (oxime type) is present in 5.1 parts by weight. The following acid-producing agent PAG-2, 3.0 parts by weight The following polymer M-1 5.1 parts by weight The above-mentioned vertically oriented liquid crystal compound alignment agent S01 is 1.9 parts by weight. The following photo-oriented polymer A-2, 0.8 parts by weight The above stabilizer DIPEA 0.2 parts by weight 93.8 parts by weight of methyl ethyl ketone 372.0 parts by weight of methyl isobutyl ketone ――――――――――――――――――――――――――――――――

[0174] Polymerization initiator S-1

[0175] [Chemical Formula 24]

[0176] Acid-producing agent PAG-2

[0177] [Chemical Formula 25]

[0178] Polymer M-1 (weight-average molecular weight 60,000. This indicates the content (mass%) of each repeating unit relative to all repeating units in the polymer.)

[0179] [Chemical Formula 26]

[0180] Photooriented polymer A-2 (in the following formula: a~c is a:b:c=17:64:19, representing the content (mass%) of each repeating unit in the polymer relative to all repeating units. The weight-average molecular weight is 100,000.)

[0181] [Chemical Formula 27]

[0182] (Fabrication of phase retardation film A13) UV light (ultra-high pressure mercury lamp; UL750; manufactured by HOYA Corporation) passing through the wire grid polarizer was applied to positive plate C2, producing 7.9 mJ / cm². 2 (Wavelength: 313nm) thus obtaining a strip-shaped film with an orientation-controllable composition layer formed on the surface. The film is continuously conveyed without being wound up, while the phase retardation film forming composition A5 is coated onto the positive C plate C2 using a die coater, and heated with warm air at 130°C for 60 seconds. Then, the obtained composition layer is subjected to UV irradiation (300 mJ / cm²) at 120°C. 2 The orientation of the liquid crystal compound was fixed to form a phase retardation film A13, thereby obtaining a laminate F13 consisting of a phase retardation film A13 / positive C plate C2 / cellulose acetate film (1) stacked sequentially. In the phase retardation film A13, Re(550) = 138 nm, Re(450) / Re(550) = 0.86, and birefringence Δn = 0.046. The laminate F13 described in Example 1 was replaced by the laminate F13 described above. Otherwise, a circular polarizer P13 was fabricated using the same method as in Example 1. An organic EL display device was fabricated using the above method, and the reflectivity and color uniformity were evaluated. The results showed that the reflectivity was A and the color uniformity was B, both of which performed well.

[0183] <Example 14> The positive C-plate forming composition C2 described in Example 13 was replaced with the following positive C-plate forming composition C3, and the phase retardation film forming composition A5 was replaced with the following phase retardation film forming composition A14. Otherwise, a laminate F14, in which phase retardation film 14 / positive C-plate 14 / cellulose acetate film (1) are sequentially stacked, was prepared using the same method as in Example 14. In phase retardation film A14, Re(550) = 138 nm, Re(450) / Re(550) = 0.86, and birefringence Δn = 0.046.

[0184] ―――――――――――――――――――――――――――――――― Composition C3 for forming positive C plates ―――――――――――――――――――――――――――――――― 100 parts by weight of the above-mentioned rod-shaped liquid crystal compound RLC-1 Polymerizable monomer (A-400, manufactured by SHIN-NAKAMURA CHEMICAL CO, LTD.) 4.2 parts by weight The above-mentioned polymerization initiator S-1 (oxime type) 5.1 parts by weight The following acid-producing agent PAG-2, 3.0 parts by weight The following polymer M-2 4.0 parts by weight The above-mentioned vertically oriented liquid crystal compound alignment agent S01 is 1.9 parts by weight. 0.8 parts by weight of the above photooriented polymer PA-1 0.2 parts by weight of diisopropylethylamine 93.8 parts by weight of methyl ethyl ketone 372.0 parts by weight of methyl isobutyl ketone ――――――――――――――――――――――――――――――――

[0185] Polymer M-2 (weight-average molecular weight 52,000. This indicates the content (mass%) of each repeating unit relative to all repeating units in the polymer.)

[0186] [Chemical Formula 28]

[0187] ―――――――――――――――――――――――――――――――― Composition A14 for phase retardation film formation ―――――――――――――――――――――――――――――――― 90.0 parts by mass of the above compound I-1 10.0 parts by weight of the above rod-shaped compound RLC-2 Photopolymerization initiator NCI-831 (manufactured by ADEKA CORPORATION) 0.5 parts by weight The above leveling agent L-1, 0.1 parts by weight 140.0 parts by weight of tetrahydrofuran Cyclopentanone 140.0 parts by weight ――――――――――――――――――――――――――――――――

[0188] Using the aforementioned PVA-based adhesive, the phase retardation film A14 of the elongated laminate F14 was adhered to one side of the polarizer (1) described in Example 1, and the polarizer protective film, composed of a cellulose triacetate film TJ25 that had undergone alkali saponification treatment, was adhered to the other side of the polarizer (1), thereby fabricating a circular polarizer P14. An organic EL display device was fabricated using the above method, and the reflectivity and color uniformity were evaluated. The results showed that the reflectivity was A and the color uniformity was B, both of which performed well.

Claims

1. A phase retardation film, which is a phase retardation film formed using a composition comprising a compound represented by formula (I), wherein, The in-plane retardation at a wavelength of 550 nm is 100–180 nm. The in-plane delay Re(450) at a wavelength of 450 nm and the in-plane delay Re(550) at a wavelength of 550 nm satisfy the relationship of equation (X). The birefringence Δn of the phase retardation film at a wavelength of 550 nm is 0.040–0.

070. Formula (X) Re(450) / Re(550)≤1.00 Formula (I) R 1 -(A 1 -L 1 ) m1 -G-(L 2 -A 2 ) m2 -R 2 In the formula, R 1 and R 2 Each of the following independently represents a straight-chain or branched alkyl group having 1 to 12 carbon atoms, or a group represented by formula (II), wherein one or more non-adjacent -CH2- groups in the straight-chain or branched alkyl group having 1 to 12 carbon atoms may be independently replaced by -O-, -COO-, -OCO-, or -O-CO-O-. Among them, R 1 and R 2 At least one of them represents a group represented by formula (II). Formula (II) P-Sp-L 3 - In the formula, P represents any group represented by formula (P-1) to formula (P-3), and the groups in formula (P-1) to formula (P-3) are... Indicates the bonding location, Sp represents an alkylene group with 1 to 10 carbon atoms or a single bond. L 3 This indicates -O-, -COO-, -OCO-, or a single bond. In formula (II) Indicates the bonding location, A 1 and A 2 Each of these terms independently represents a 1,4-phenylene that can be substituted with one or more substituents S, a 1,4-cyclohexylene that can be substituted with one or more substituents S, or a naphth-2,6-diylene that can be substituted with one or more substituents S. 1 When multiple instances exist, they can be the same or different. A 2 When multiple instances exist, they can be the same or different. The substituent S represents a fluorine atom, a chlorine atom, a straight-chain alkyl group having 1 to 8 carbon atoms, or a straight-chain alkoxy group having 1 to 8 carbon atoms. L 1 and L 2 Each can independently represent -O-, -OCH2-, -CH2O-, -CH2CH2-, -COO-, -OCO-, -COO-CH2CH2-, -OCO-CH2CH2-, -CH2CH2-COO-, -CH2CH2-OCO-, or a single bond, L 1 When multiple instances exist, they can be the same or different, L 2 When multiple instances exist, they can be the same or different. Among them, at least one of the following conditions must be met: -A directly bonded to G 1 -L 1 - represents the group represented by formula (V-1), and -L is directly bonded to G. 2 -A 2 - represents the group indicated by formula (V-2), 1 indicates the bonding position with G. G represents a group represented by any one of formulas (G-1) to (G-7). Indicates the bonding location, T represents the group represented by formula (T), Indicates the bonding location, In formulas (G-1) to (G-7), these groups can be substituted with substituents. W represents a hydrogen atom or a straight-chain alkyl group having 1 to 12 carbon atoms, wherein one or more -CH2- atoms or two or more non-adjacent -CH2- atoms in the straight-chain alkyl group may be independently substituted with -O- atoms, and the straight-chain alkyl group may have substituents. Y represents a hydrogen atom, a straight-chain alkyl group having 1 to 20 carbon atoms, or a branched alkyl group having 1 to 20 carbon atoms. R 3 This refers to a straight-chain alkyl group containing hydrogen, fluorine, or chlorine atoms, or a straight-chain alkoxy group containing 1 to 8 carbon atoms. m1 and m2 each independently represent 1 or 2.

2. The phase retardation film according to claim 1, wherein, The composition also contains a compound with positive wavelength dispersive properties.

3. The phase retardation film according to claim 2, wherein, The birefringence Δn of the positive wavelength dispersive compound at a wavelength of 550 nm is 0.050 to 0.

100.

4. The phase retardation film according to any one of claims 1 to 3, wherein, The composition contains two or more compounds represented by the formula (I).

5. The phase retardation film according to any one of claims 1 to 3, wherein, The composition also contains a polyfunctional monomer.

6. The phase retardation film according to any one of claims 1 to 3, wherein, The composition also contains polyfunctional thiols.

7. The phase retardation film according to any one of claims 1 to 3, wherein, The content of the compound represented by the formula (I) is less than 85% by mass relative to the total solids content in the composition.

8. The phase retardation film according to any one of claims 1 to 3, wherein, The composition also contains an oxime initiator.

9. The phase retardation film according to any one of claims 1 to 3, wherein, The composition also contains a leveling agent. The leveling agent content is 0.01 to 0.1% by mass relative to the total mass of the liquid crystal compound in the composition.

10. The phase retardation film according to any one of claims 1 to 3, wherein, The residual rate of polymeric groups is less than 30%.

11. A polarizer comprising a phase difference film and a polarizer as described in any one of claims 1 to 10.

12. The polarizer according to claim 11, wherein, It also includes the C-plate.

13. The polarizer according to claim 11, wherein, It also includes an alignment film disposed adjacent to the phase difference film.

14. A display device comprising the polarizer of claim 11.

Citation Information

Patent Citations

  • polymerizable liquid crystal compound

    JP1999513019A

  • Liquid crystal compound, liquid crystyal composition, polymer, retardation plate, and elliptical polarization plate

    JP2005289980A